Speaking (Oxford University Press, 1997)
How do learners learn to speak a foreign language? What differentapproaches have been developed to teach this important skill? Speaking dealswith both these questions, providing clear explanations of recent research anddevelopments in methodology. In the final section the author suggests practicalways in which teachers can gain a better understanding of the role of oralclassroom activities.